Quantitative analysis of knowledge, attitude and practice of workers in chicken slaughter slabs toward food safety and hygiene in Ouagadougou, Burkina Faso - Assefa, Ayalew; Dione, Michel M.; Ilboudo, Guy S.; Lallogo, Valérie R.; Gemeda, Biruk A.; Grace, Delia; Knight-Jones, Theodore J.D. (Frontiers Media, 2023)
Introduction: In low- and middle-income countries, chicken serves as a cheap source of protein and an income source for many households. It is particularly important in the capital, Ouagadougou, Burkina Faso, where chicken is regularly consumed. However, hygiene standards are very low, posing a significant public health risk.